HUBUNGAN PENGETAHUAN KADER DENGAN PENERAPAN MANAJEMEN TERPADU BAYI MUDA (MTBM) DI WILAYAH KERJA PUSKESMAS KECAMATAN DARUL IMARAH KABUPATEN ACEH BESAR - Elmiyati Elmiyati; Salami Salami (Jurnal Sains Riset, 2021)
The success of the posyandu cannot be separated from the hard work of cadres who voluntarily manage the posyandu in their respective areas. The purpose of the study was to determine the relationship between Cadre Knowledge and the Application of Integrated Management of Young Infants (MTBM) in the Working Area of the Public Health Center, Darul Imarah District, Aceh Besar District. The design of this study used a descriptive correlational design using a cross sectional approach. The sampling technique used in this study was random sampling with a total population of 217 and the sample amounted to 68 cadres in the working area of the Darul Imarah district health center, Aceh Besar district. The research instrument used was a questionnaire. The time of data collection was from 1 to 24 December 2018. Data analysis included univariate and bivariate analysis. The results showed that the relationship between cadres' knowledge about the meaning of MTBM with the implementation of MTBM, after statistical tests (chi-square test), obtained p-value = 0.003 (p-value 0.05), there was a relationship between cadres knowledge about the goals of MTBM with implementation of MTBM, after statistical tests (chi-square test), obtained p-value = 0.006 (p-value 0.05), there is a relationship between cadres' knowledge about MTBM implementation and MTBM implementation, after statistical tests (chi-test) square), obtained p-value = 0.009 (p-value 0.05), there is a relationship between cadres' knowledge about the actions and treatment of MTBM with the implementation of MTBM, after statistical tests (chi-square test), obtained p-value = 0.009(p-value0.05). In general, it can be concluded that there is a relationship between the knowledge of cadres and the implementation of MTBM in the working area of the Puskesmas Darul Imarah District, Aceh Besar District. It is recommended for cadres to try to increase their knowledge about their duties as cadres, especially regarding child development. Try to find more information from other health workers even though they are outside the posyandu.Keywords: MTBM, Toddler, Cadre knowledge